The Role of Islamic Religious Education Teachers in Preventing Juvenile Delinquency at Budi Agung Private High School Medan - Nabilla Amalia; Arlina Arlina (Edumaspul: Jurnal Pendidikan, 2023)
In this globalized world, juvenile delinquency and other lawlessness are common news. In addition, many teenagers commit fights and murders. This study examines how PAI teachers at SMA Swasta Budi Agung Medan reduce juvenile delinquency as well as the supporting and inhibiting variables. Thus, PAI teachers can foster children to identify their problems and prevent juvenile delinquency in this day and age. Every educator can instill Islamic ideals from the Qur'an and Hadith in their students. Thus, this study examines the involvement of PAI teachers in preventing juvenile delinquency at SMA Swasta Budi Agung Medan to prevent environmental and national crimes. This research uses descriptive qualitative method with phenomenological approach to collect primary data through observation and in-depth interview as well as secondary data from journals, books, and articles. The results of the research regarding the prevention of juvenile delinquency with optimal Islamic religious education. Prevention of juvenile delinquency includes including adolescents in religious activities and other good activities to build character.